ANALISIS EROSI DAN KEMAMPUAN LAHAN UNTUK ARAHAN PENGGUNAAN LAHAN DENGAN METODE PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS (Kasus di DAS Nunkurus,Kabupaten Kupang, Provinsi Nusa Tenggara Timur - , YOFRIS PUAY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nunkurus watersheed is one of the watersheed that located in Kupang, NTT Province. Generally, this watersheed has type E in climate that israther dry . But it does not mean that Nunkurus watershed free from the danger of erosion. High intensity rainfall that occurs during the rainy and slope will increase the risk and danger of erosion.This is further supported by soil treatment activities and grazing that do not noticed the principles of conservation and the capability of the land This research aims to :1) Determine the rate of erosion and dangerous of erosion in Nunkurus watersheed. 2) Arrange land capab ility classification in Nunkurus watershed 3 ) Provide general overview and recommendations in land use direction that appropriate toland capability in Nankurus watershed. Data collection be primary and secondary data. The primary data be soil sampling to determine the value of soil erodibility. Secondary data were taken in the form of rainfall data from Camplong , Naibonat, Oekabiti, and Lasiana S tations to calculate the value of erosivity. Other secondary data that taken are landuse, soil conservation, slope, soil drainage, rock/gravel , the threat of flooding and solum. Erosion calculation using USLE method and determining land capability using LCLP software. Spatial mapping using ArgGis 10.3 and ArcView 3.3 software. Processing of attribute data using Microsoft Office Excel. The research result show that:1) The level of erosion in Nunkurus watersheed dominated by Class I(<15 tons/ha/yr) covering an area of 138,80 km 2 . And then Class II covering 36,31 km 2 , Class V covering 10,43 km 2 , Class III covering 5,84 km 2 and Class IV covering 3,73 km 2 . 2) land capability classes in Nunkurus watershed are Land Capability Class IV, ClassVI, and Class VII. Land capability classes VI dominate in Nunkurus watershed c overing 180,55 km 2 or 92,53% of the total study area. Class IVcovering 3,06 km 2 and Class VII covering 11,50 km 2 or 5,90 % of the study area. 3) Land use recommendations for Class IV are limited grazing, selective cutting by following the principles of soil and water conservation , Class VII, recommended for pasture or forest